Staring and Perceptions Towards Persons with Facial Disfigurement - Halioua, Rebecca Leigh (East Carolina University, 2010)
A convenience sample of college students (N=33) enrolled in courses in the College of Health and Human Performance at East Carolina University was used to determine if there were statistically significant relationships between staring and perceptions of people with facial disfigurement. Staring was measured by fixation time in seconds with an Applied Sciences Laboratories (ASL, Watham, MA) 6000 SU eye movement system with Eyehead Integration Software and GazeTracker to see if participants spent more time fixating on people with facial disfigurement than people without facial disfigurement when presented with four photos on a computer monitor. Perceptions of people were measured by the Facial Disfigurement Photograph Scale, a Likert-type scale which measures perceptions of honesty, employability, intelligence, trustworthiness, attractiveness, optimism, effectiveness, popularity, and capability based on a person's appearance in a photo. Results indicated that people with facial disfigurement (M=3.2, SD=1.7) were stared at longer than people without facial disfigurement (M=2.7, SD=1.3); t=-2.25, p<.05. However, only the perception of capability of people with facial disfigurement was significantly related to staring (p<.05).
Keywords: Recreation; Gaze--Psychological aspects; Perception--Testing; Face--Abnormalities